2009
DOI: 10.1007/s12032-009-9316-7
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life and depression among metastatic breast cancer patients

Abstract: Depression is seen in many cancer patients. It is common in the general population and in adults and children with cancer and frequently coexists with anxiety and pain. The pilot study evaluated the level of the global quality of life (QoL) and the incidence and the relevance of the depression among metastatic breast cancer patients in a programme of palliative cancer care. The study is prospective and cross-sectional. Dates were obtained during year 2008 among 41 patients. The mean age of all 41 subjects was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 2 publications
0
11
0
1
Order By: Relevance
“…The difference of quality of life according to the presence or absence of breast cancer metastasis has been reported by several studies. In some studies, it has been stated that breast cancer metastasis is associated with depression and overall quality of life, and it has also been reported that the recurrence of breast cancer strongly lowered the quality of life of patients, and even their guardians 6,7. This appears to be due to a fear of additional metastasis as well as the burden of additional treatments after metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…The difference of quality of life according to the presence or absence of breast cancer metastasis has been reported by several studies. In some studies, it has been stated that breast cancer metastasis is associated with depression and overall quality of life, and it has also been reported that the recurrence of breast cancer strongly lowered the quality of life of patients, and even their guardians 6,7. This appears to be due to a fear of additional metastasis as well as the burden of additional treatments after metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…HUI-3 consists of 40 items that capture 8 attributes of health-related QoL: vision, hearing, speech, ambulation, dexterity, emotion, cognition, and pain. 31 The scoring algorithm was obtained from Health Utilities Inc. and is based on Canadian health preference weights. Utility scores from both instruments range from 0–1, with a higher score indicating better quality-adjusted life.…”
Section: Methodsmentioning
confidence: 99%
“…[14][15][16][17][18] In Korea, the prevalence of anxiety or depression in cancer patients has been estimated as 28.8~56.5% when all stages and cancer types are considered. 25,26) However, there are few studies that have focused on anxiety and depression in patients with gastrointestinal cancer, or that have reported an association between psychological distress and QOL in patients with gastrointestinal cancer.…”
Section: Discussionmentioning
confidence: 99%
“…12,13) Therefore, comprehensive and periodic patient assessment focused on psychological as well as physical aspects should be incorporated into the treatment process for cancer patients, particularly those with advanced or metastatic cancer. Although there are many studies on psychological distress and QOL in cancer patients, [14][15][16][17][18] there are few studies on the relation between psychological distress and QOL in patients with advanced or metastatic gastrointestinal cancer. 19,20) The objective of this study was to assess the factors associated with QOL, pain, anxiety, and depression were evaluated at initial diagnosis of advanced gastrointestinal cancer (study enrollment) and during the palliative treatment process (3 months after study enrollment).…”
Section: Introductionmentioning
confidence: 99%